Anesthesia Management in Scoliosis Surgery of Patients with Friedreich’s Ataxia: A Report of Four Cases - Muhammed Köse; Ercan Bal; Şemsi Mustafa Aksoy; Ayşe Lafçı (Genel Tıp Dergisi)
Friedreich's ataxia (FRDA) is an autosomal recessive neurodegenerative disease, which may be accompanied by scoliosis, cardiac, endocrine and pulmonary comorbidities. We present our anesthesia experiences using total intravenous anesthesia (TIVA) method in scoliosis surgery of four patients with Friedreich ataxia. Patients were monitored with central venous pressure (CVP), bispectral index (BIS),invasive blood pressure and near infrared spectroscopy (NIRS). The risk of malignant hyperthermia and difficult airway are increased in patients with Friedreich's ataxia. We were prepared for difficult airway and provided dantrolene preoperatively. Neuromuscular blocker was used for anesthesia induction in one case, we did not use it in the other cases. Hypertrophic cardiomyopathy may accompany patients with Friedreich's ataxia. Therefore, detailed preoperative examination, intraoperative close bleeding, blood gas analysis, hemodynamic monitoring and postoperative multimodal analgesia for hemodynamic stability in patients with Friedreich's ataxia were performed. We aimed to discuss our anesthesia management with four patients with Friedreich's ataxia who underwent scoliosis surgery.